Conventional Two-Stage Hepatectomy or Associating Liver Partitioning and Portal Vein Ligation for Staged Hepatectomy for Colorectal Liver Metastases? A Systematic Review and Meta-Analysis - Zhang, Liang; Yang, Zhentao; Zhang, Shiyu; Wang, Wenchao; Zheng, Shusen (Frontiers in Oncology, 2020)
Background: Pushing the surgical limits for initially unresectable colorectal liver metastases (CRLM) are two approaches for sequential liver resection: two-stage hepatectomy (TSH) and associating liver partitioning and portal vein ligation for staged hepatectomy (ALPPS). However, the role of each treatment modality remains ill-defined. The present meta-analysis was designed to compare the safety, efficacy, and oncological benefits between ALPPS and TSH in the management of advanced CRLM. Methods: A systematic literature search was conducted from online databases through to February 2020. Single-arm synthesis and cumulative meta-analysis were performed. Results: Eight studies were included, providing a total of 409 subjects for analysis (ALPPS: N = 161; TSH: N = 248). The completions of the second stage of the hepatectomy [98 vs. 78%, odds ratio (OR) 5.75, p < 0.001] and R0 resection (66 vs. 37%; OR 4.68; p < 0.001) were more frequent in patients receiving ALPPS than in those receiving TSH, and the waiting interval was dramatically shortened in ALPPS (11.6 vs. 45.7 days, weighted mean difference = −35.3 days, p < 0.001). Nevertheless, the rate of minor complications was significantly higher in ALPPS (59 vs. 18%, OR 6.5, p < 0.001) than in TSH. The two treatments were similar in 90-day mortality (7 vs. 5%, p = 0.43), major complications (29 vs. 22%, p = 0.08), posthepatectomy liver failure (PHLF; 9 vs. 9%, p = 0.3), biliary leakage (11 vs. 14%, p = 0.86), length of hospital stay (27.95 vs. 26.88 days, p = 0.8), 1-year overall survival (79 vs. 84%, p = 0.61), 1-year recurrence (49 vs. 39%, p = 0.32), and 1-year disease-free survival (34 vs. 39%, p = 0.66). Cumulative meta-analyses indicated chronological stability for the pooled effect sizes of resection rate, 90-day mortality, major complications, and PHLF. Conclusions: Compared with TSH, ALPPS for advanced CRLM resulted in superior surgical efficacy with comparable perioperative mortality rate and short-term oncological outcomes, while this was at the cost of increased perioperative minor complications.